Gut microbiota and risk of coronary heart disease: a two-sample Mendelian randomization study - Hu, Xiang-zhi; Fu, Ling-ling; Ye, Bin; Ao, Man; Yan, Ming; Feng, Hong-chao (Frontiers in Cardiovascular Medicine, 2024)
The relationship between gut microbiota composition and coronary heart disease (CHD) has been recently reported in several observational studies. However, the causal effect of gut microbiota on Coronary heart disease is uncharted.OBJECTIVE: This study attempted to investigate the effect of gut microbiota on coronary heart disease by Mendelian randomized analysis. METHODS: Through the two-sample MR method, single nucleotide polymorphisms (SNPs) relevant to gut microbiota were selected as instrument variables (IVs) to evaluate the causal association between gut microbiota and the risk of CHD.RESULTS: According to the selection criteria of inverse-variance-weighted (IVW) that Class.